PEMBERDAYAAN KELUARGA DALAM MENCEGAH KEGAWATDARURAT STROKE DI WILAYAH KERJA PUSKESMAS MARTAPURA 1 - Nurhayati; Roswita, Ria; Jannah, Raudatul (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Stroke is one of the non-communicable diseases (NCDs) that causes major deaths worldwide. According to WHO, deaths due to cardiovascular disease are caused by 2 main diseases, namely ischemic heart disease and stroke. South Kalimantan Province is a province that has a high percentage of stroke incidence, reaching 12.7%. The incidence of stroke in Banjar Regency in 2021 reached 137 people and the number of deaths reached 27 people. Prehospital treatment for stroke attacks can reduce morbidity and mortality. The focus of prehospital treatment for stroke attacks is time is brain and the golden hour. Prehospital treatment for stroke patients is still very weak, one of the reasons being the lack of public knowledge about early detection of stroke emergencies. Education and counseling about early detection of stroke emergencies need to be provided to patients and their families. The community service activities carried out first formed a stroke care family group, then counseling and training were carried out related to the prevention of stroke emergencies. The results of community service showed an increase in the average before and after education, namely 7.1 to 10.2. From these results, education about early detection of stroke can increase knowledge so that it can prevent stroke emergencies using the FAST method.